Late Cretaceous‐Recent Tectonostratigraphic Evolution of the Yucatan Back‐Arc Basin, Northern Caribbean Sea - Juan Pablo Ramos; Paul Mann (Geochemistry, Geophysics, Geosystems, 2023)
Abstract The 110,000 km2 Yucatan Basin in the northern Caribbean Sea is critical for understanding the Late Cretaceous to Recent tectonic evolution of the Caribbean‐North American plate boundary. This study integrates gravity, magnetic, and a 5,500 km grid of 2D seismic data to carry out a tectonostratigraphic analysis of the Yucatan Basin. These data provide the first recognition of 38–102 km‐long spreading ridges that constrain a SW‐NE opening direction in the western Yucatan Basin. The age of this oceanic crust is constrained to be late Paleocene‐middle Eocene (57–42 Ma) based on heat flow measurements, depth‐to‐seafloor, and three sedimentary sequences inferred to be Eocene—Recent in age based on stratigraphic correlations to distant wells. We interpret the Yucatan Basin as a back‐arc basin formed during the northeastward movement of the Caribbean volcanic arc that is now exposed in Cuba, evolved during the early Cretaceous to middle Eocene, and was terminated by collision with the Bahama carbonate platform during the late Paleocene to middle Eocene. We identify regional, left‐lateral strike‐slip faults that extend into the Cuban volcanic arc, as observed in other active back‐arc basins. We propose that the Yucatan back‐arc basin once formed the northwestern extension of age‐equivalent back‐arc basins in Hispaniola, where the basin is inverted, topographically elevated, and strongly shortened, and in the Lesser Antilles where the Paleogene back‐arc basin has remained undeformed and submarine. This once‐continuous back‐arc basin was disrupted and left‐laterally offset by ∼500 km during the Late Eocene‐Recent formation of the Cayman trough strike‐slip system.